Remembrance - Ben Arbaugh - Shea, Peter (Online Learning, 2018)
On June 16th, 2018 family, friends, and the world of online learning scholarship lost Dr. John Benard Arbaugh, known to everyone as “Ben”. Ben was a pioneer in online learning with more than 80 publications including 17 best article or best paper awards. Ben was also a member of the OLJ Editorial Board. Many of us knew Ben for his scholarship on the Community of Inquiry model and for his work as an evaluator on national projects such as the Predictive Analytics Framework (PAR). Ben’s passing is felt by the many colleagues and coauthors with whom he worked around the world. He was a true mentor, teacher, scholar and friend. We will miss him.